"Umbilical mass": a case of primary umbilical endometriosis and literature review - Jian-Zhong Pan; Yan Tang; Ling Li; Xin-Yue Xu; Xiao Cheng; Yuan-Yuan Chen (IMR Press, 2021)
Background: To report on a case of primary Umbilical Endometriosis (PUE). Case: We report a new rare case of PUE in a 45-year-old woman arising in the umbilicus, presenting as three purple-blue firm masses with a smooth surface, and clear borders. The patient presented to our hospital with a complaint of dark-red blood flowing out of the umbilical fossa accompanied by periodic menstrual pain for more than a year. PUE was initially diagnosed based on clinical signs and imaging studies and the mass was widely excised. The postoperative histologic examination of the tissue confirmed the diagnosis of PUE. Conclusion: PUE is a rare umbilical disorder. Its diagnosis may be complicated due to clinician lack of knowledge. The possibility of endometriosis must be considered during the evaluation of an umbilical mass despite the absence of any previous surgery, with special attention to menstrual symptoms or bloody discharge.